Delivering Service Indicators in Education and Health in Africa : A Proposal - Bold, Tessa; Gauthier, Bernard; Svensson, Jakob; Wane, Waly (2012)
The Delivering Service Indicators seek to provide a set of indices for benchmarking service delivery performance in education and health in Africa in order to track progress in and across countries over time. It seeks to enhance effective and active monitoring of service delivery systems and to become an instrument of public accountability and good governance in Africa. The main perspective adopted by the Delivering Service Indicators index is one of citizens accessing services and facing potential shortcomings in those services available to them. The index is thus presented as a Service Delivery Report Card on education and health. However, unlike traditional citizen report cards, it assembles objective information from micro level surveys of service delivery units.